1999
DOI: 10.1136/bjo.83.6.652
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus retinitis after the initiation of highly active antiretroviral therapy: a 2 year prospective study

Abstract: Background/aims-There have been several recent reports suggesting that the natural history of cytomegalovirus retinitis (CMVR) has been significantly modified with the development of highly active antiretroviral therapy (HAART). This 2 year prospective cohort study assesses the eVect of HAART on the incidence and progression of CMV retinitis in patients with CD4 cell counts below 50 cells ×10 (Br J Ophthalmol 1999;83:652-655)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The increase of a CD4 cell count >100 mm −3 requires regularly more than 6 months after initiation of HAART. Particularly during the initial months of antiretroviral treatment and before full reconstitution of cellular immunity patients are still at high risk of developing CMV disease (Ledergerber et al, 1999;Salmon-Ceron et al, 2000;Mitchell et al, 1999;Jacobson et al, 2000). In addition, CD4 cell counts remain below the critical threshold of 100 mm −3 in 10-20% of patients treated with HAART (Kaufmann et al, 2003).…”
Section: Is CMV Still An Issue?mentioning
confidence: 98%
“…The increase of a CD4 cell count >100 mm −3 requires regularly more than 6 months after initiation of HAART. Particularly during the initial months of antiretroviral treatment and before full reconstitution of cellular immunity patients are still at high risk of developing CMV disease (Ledergerber et al, 1999;Salmon-Ceron et al, 2000;Mitchell et al, 1999;Jacobson et al, 2000). In addition, CD4 cell counts remain below the critical threshold of 100 mm −3 in 10-20% of patients treated with HAART (Kaufmann et al, 2003).…”
Section: Is CMV Still An Issue?mentioning
confidence: 98%
“…Highly active antiretroviral therapy (HAART), which combines reverse transcriptase-inhibiting nucleosides with human immunodeficiency virus type 1-specific protease inhibitors, has been shown to promote the regression of several opportunistic infections, including CMV retinitis [2,4,18,20,27,29]. It has been reported that discontinuation of maintenance therapy might be considered in patients with HAART-induced elevated CD4+ counts above 100 cells/µl and completely quiescent retinitis characterized by retinal pigment epittelium (RPE) scarring only [29].…”
Section: Introductionmentioning
confidence: 98%
“…In the post-HAART era, we have witnessed an important decrease in CMV disease incidence among AIDS patients 4,8,27,33,46 . However, CMV infection remains an event associated with high morbidity and mortality rates, justifying every effort to understand the interaction between the virus and its host.…”
Section: Discussionmentioning
confidence: 99%